VASCULAR REMODELING IN HYPERTENSION: ANGIOGENESIS FEATURES - L. A. Haisheva; S. V. Shlyk; A. S. Pleskachev; E. S. Makarenko (Klinicist, 2014)
Aim — cross-sectional study of changes in various segments of the vascular bed in arterial hypertension (AH), defining the role of inducers and inhibitors of angiogenesis in these processes.Materials and methods. The study included 99 patients with arterial hypertension of I–II degree, average age of 63.2 ± 2.6 years, diseaseduration 9.2 ± 7.2 years.Results. It was found that patients with arterial hypertension have disorders in all segments of vascular bed: endothelial dysfunction (highvWF), microcirculatory disorders, and increased pulse wave velocity (PWV) of elastic-type vessels. The level of angioginesis factors doesnot depend on such parameters as gender, age, body mass index. Smoking and duration of hypertension influence on vascular endothelialgrowth factor raise and endostatin levels are higher in patients with family history of cardiovascular diseases. Duration of disease is directlycorrelated with microcirculatory disorders and the PWV, correlation between microcirculatory disorders and pulse wave velocity indicatetheir common processes.